2006
DOI: 10.1088/0953-8984/18/42/006
|View full text |Cite
|
Sign up to set email alerts
|

New orthorhombic modification of equiatomic CePdAl

Abstract: The crystal structure of a new low-temperature modification of CePdAl was determined from single-crystal x-ray data: CePdAl-type; space group Pmmn (No. 59), Z = 14, oP42, a = 0.426 07 nm, b = 2.887 58 nm, c = 0.721 90 nm; R F = 0.048. Physical properties of orthorhombic CePdAl are governed by a mutual balance of the RKKY interaction, the Kondo effect and crystalline electric field splitting, resulting in antiferromagnetic ordering below ≈2.5 K. Electronic transport is reminiscent of a textbook-like Kondo latti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Compared to CeRu 1– x Ni x Al ( x = 0.1–0.8) the structure type persists a little further over the full range from x = 0.1–0.9. This might be due to the fact that CePdAl is reported to crystallize in a second orthorhombic modification with its own structure type (CePdAl, Pmmn , a = 426.1, b = 2887.6, c = 721.9 pm21). This modification of CePdAl shows a significant structural relationship to the LaNiAl type structure and can be explained as a combination of structural elements of LaNiAl, which get separated by ZrNiAl type fragments (Figure 1, bottom).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to CeRu 1– x Ni x Al ( x = 0.1–0.8) the structure type persists a little further over the full range from x = 0.1–0.9. This might be due to the fact that CePdAl is reported to crystallize in a second orthorhombic modification with its own structure type (CePdAl, Pmmn , a = 426.1, b = 2887.6, c = 721.9 pm21). This modification of CePdAl shows a significant structural relationship to the LaNiAl type structure and can be explained as a combination of structural elements of LaNiAl, which get separated by ZrNiAl type fragments (Figure 1, bottom).…”
Section: Resultsmentioning
confidence: 99%
“…CeRuAl exhibits intermediate valence behavior without any magnetic ordering down to 2 K,4 whereas β‐CePdAl (ZrNiAl type) shows an antiferromagnetic phase transition at T N = 2.7 K 22,23. Within its own type structure α‐CePdAl orders antiferromagnetically at even lower temperatures ( T N < 2.5 K) 21. In contrast to the reported two CePdAl phases no magnetic ordering down to 2.5 K could be observed even in low‐field studies for all investigated samples of the reported solid solution.…”
Section: Resultsmentioning
confidence: 99%
“…The next chemical element following Rh in the periodic table, palladium, also forms an equiatomic ternary compound when reacting with Ce and Al-CePdAl. This compound crystallizes in two polymorphic modifications: high-temperature hexagonal [11] and low-temperature orthorhombic crystal structures [12]. CeRuAl and CeRhAl are closely related to the high-temperature hexagonal modification of CePdAl [11] (ZrNiAl type, space group P-62m (No.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain a more reliable estimate for the trend of the Kondo energies in CeNi 9−x Cu x Ge 4 we utilized the resonant-level model by Schotte and Schotte [28] in combination with a molecular field approach to account for long-range magnetic order [29,30].…”
Section: Analysis Of the Low Temperature Specific Heatmentioning
confidence: 99%